2018
DOI: 10.1111/jfs.12488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Shiga‐toxin producing Escherichia coli isolated from meat products sold in San Luis, Argentina

Abstract: Shiga toxin‐producing Escherichia coli (STEC) in meat products was studied by four procedures which combined enrichment, immunomagnetic separation (IMS), plating, and a stx screening polymerase chain reaction. A total of 167 samples (57 ground beef, 58 fresh sausages, and 52 precooked sausages) were collected from retail markets in San Luis, Argentina. The number of stx‐positive samples represented 11.4% of the total (19/167) distributed as follows: seven for raw ground beef (12.3%), six for precooked sausages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…One of the most common STEC vehicles is beef, followed by pork, both frequently associated with STEC outbreaks (Scott et al., 2020; Smith & Fratamico, 2018). Here, we registered the presence of STEC in 2.3% of beef, 2.0% of pork and 1.3% of ground beef, whereas previous studies have reported its presence between 2.7% and 12.3% in meat internationally (Li et al., 2011; Salinas‐Ibáñez et al., 2018; Varcasia et al., 2018). Thus, our isolation rates are lower than those previously reported, which may be due to seasonal and geographical variations (González‐Escalona & Kase, 2019), and also to the high biosecurity measures currently used in animal husbandry and slaughterhouses in Chile (MINAGRI, 2013; INIA & INDAP, 2017; SAG, 2019).…”
Section: Discussionmentioning
confidence: 52%
“…One of the most common STEC vehicles is beef, followed by pork, both frequently associated with STEC outbreaks (Scott et al., 2020; Smith & Fratamico, 2018). Here, we registered the presence of STEC in 2.3% of beef, 2.0% of pork and 1.3% of ground beef, whereas previous studies have reported its presence between 2.7% and 12.3% in meat internationally (Li et al., 2011; Salinas‐Ibáñez et al., 2018; Varcasia et al., 2018). Thus, our isolation rates are lower than those previously reported, which may be due to seasonal and geographical variations (González‐Escalona & Kase, 2019), and also to the high biosecurity measures currently used in animal husbandry and slaughterhouses in Chile (MINAGRI, 2013; INIA & INDAP, 2017; SAG, 2019).…”
Section: Discussionmentioning
confidence: 52%